A Step Toward A Hyperintellectual Society - Primov Baxriddin Abdiraxmonovich (Pubmedia Social Sciences and Humanities, 2026)
This article examines the transitional period in which society is moving toward a new stage of development and explores the ongoing process of digitalization emerging in the interaction between humans and Artificial Intelligence (AI). In this context, we discuss the concept of a hyperintellectual society as a prospective stage of social evolution. In the contemporary information age, providing a theoretical foundation and explanation for such transformations is considered a highly relevant scientific task. These ideas are expected to attract the interest of readers and encourage deeper reflection on the future trajectory of human civilization.